Presentations and Psychiatric Diagnosis in A Psychiatric Out-Patient Clinic of Tertiary Care Hospital in Eastern Nepal - Shakya, Dhan Ratna; Kafle, Sujan; Dawadi, Suyash; Khatri, Arun; Sah, Mithun (Journal of Psychiatrists’ Association of Nepal, 2021)
INTRODUCTION This study aimed to see common presenting complaints and psychiatric diagnoses among the patients visiting for the first time to the Psychiatric Out-patient Department (OPD) of a tertiary care hospital in Eastern Nepal. METHODOLOGY A cross-sectional study was conducted in the OPD of B.P. Koirala Institute of Health Sciences (BPKIHS), Dharan, Nepal during the study period of 3 weeks after the institute ethical approval. Patients were selected via convenience sampling technique. Face to face interview was conducted to collect socio-demographic data and the presenting complains (up to 5) according to the patients and their attendants. Psychiatric diagnoses were recorded as per the clinician. RESULT Among the first contact psychiatry out-patients; various physical/ somatic, anxiety and mood related symptoms were the commonest presenting complaints, as per the patients, attendants and clinicians. Behavioural symptoms were others mostly observed and reported. The commonest diagnoses were: Depression, Recurrent Depressive Disorder, Dysthymia (18.6%); Phobia, Other Anxiety and Obsessive Compulsive Disorder (17.9%); Schizophrenia, schizotypal and delusional disorders (13.8%) and Mental and Behavioural disorders due to Substance use (8.3%). Deliberate self harm and seizures were present in 7% each. CONCLUSION The commonest presenting complaint in psychiatry outpatient clinic was related to physical and somatic symptoms, followed by anxiety and mood related ones. Common diagnoses were Depression, Anxiety, Schizophrenia and Substance use/ related disorders.